UTILIZATION OF MATERNAL HEALTH CARE SERVICES IN SOUTH INDIA - Navaneetham, K (Centre for Development Studies-WP307, 2000)
In this study we examine the patterns and determinants of maternal health care use across different social setting in south India: in the states of Andhra Pradesh, Karnataka and Tamil Nadu. We use data from the National Family Health Survey (NFHS) carried out during 1992-93 across most states in India. The study focuses on most recent births to evermarried women that took place during the four years prior to the date of the survey. We have used logistic regression models to estimate the effect of covariates on the utilization of maternal health services viz., antenatal care, tetanus toxoid vaccine, place of delivery and assistance during delivery. The study indicates that determinants of maternal health care services are not same across states and for different maternal health care indicators. Although illiterate women were less likely to use maternal health care services; there was no difference among the educated. The level of utilization of maternal health care services was found to be highest in Tamil Nadu, followed by Andhra Pradesh and Karnataka. Part of the interstate differences in utilization is likely to be due to differences in availability and accessibility among the three south Indian states. It is argued that the differential in access to health care facilities between rural-urban areas is an important factor for lower utilization of maternal health care services, particularly for institutional delivery and delivery assistance by health personnel in the rural areas of the three states. Results from this study indicate that health workers might play a pivotal role in providing antenatal care in the rural areas.